ENSURING STATE SECURITY THROUGH THE PRISM OF INTERACTION OF THE NATIONAL GUARD OF UKRAINE WITH OTHER SUBJECTS OF THE SECURITY AND DEFENSE SECTOR - Koba, Oleksandr; Dudurych, Vasyl (Honor and Law, 2023)
The article analyzes the content and essence of the concept of state security through the prism of interaction of the National Guard of Ukraine with other subjects of the security and defense sector. A number of scientific, theoretical and practical recommendations of organizational content to optimize the functioning of the relevant process are provided. The author substantiates that ensuring the state security is directly within the competence of all subjects of the security and defense sector of Ukraine, and in the conditions of active hostilities against the invader, the issue of consolidation of all forces and means available in this segment, including such a state authority as the National Guard of Ukraine, which at the same time being law enforcement, was established as a military formation, becomes particularly relevant. The author characterizes the content and essence of the concept of state security and outlines the mechanism for its provision, defining the role and place in it of the security and defense sector as a whole, as well as the National Guard of Ukraine as a central executive body and one of the relevant subjects. In addition, it is substantiated that the Law of Ukraine "On the National Guard of Ukraine" defines the legal status and range of its main powers, which directly form the field of competence in the activities of the relevant unit of the security and defense sector of Ukraine, but taking into account the critically large number of Ukraine's needs related to the implementation of both military and law enforcement (stabilization) measures, the issue of effective interaction of the National Guard of Ukraine with others becomes more urgent subjects of the security and defense sector of Ukraine. The prospect of further scientific research is to outline international analogues of mechanisms for ensuring state security by several actors at once, which takes place in the order of interaction, analysis of relevant empirical material and discussion of ways to implement relevant models in the national legal field.